Examining the magic of proximity in Shafi’i Kadkani’s A Mirror for Sounds - mina zadkhoot; Heydar Hasanloo; nazhat noohi; Hosein Arian (مطالعات زبانی و بلاغی)
The understanding of the hidden layers in the text is determined by the use of signs. Signs consist of a phonetic form (signifier) and a conceptual idea (signified) that alone express meaning and concept. The phonetic harmony and balance between the words creates a new meaning, which implies that the music created through the unity or contrast of the consonants and vowels of the words is in harmony with the poet’s intended meaning. The present essay tries to investigate the magic of proximity in A mirror for Sounds. This research was done based on the concept of the magic of proximity in Shafi’i Kadkani's aforementioned collection, using a descriptive-analytical method through a library and survey approach. The findings of the research show that the poet has increased the beauty and effectiveness of his speech by a balanced, accurate and coherent use of devices. He employs a variety of figurative devices to convey imagery, emotion i and sound, which has made his poetry specially graceful. Also, Shafi'i Kadkani has paid special attention to this literary genre (the magic of proximity) in his collection of poems, attracting the attention of many readers. In addition, the most literary use of "magic of proximity" in poetry, after alliteration, is to induce feelings, and the magic of proximity has an effective role and a high position in shaping and strengthening the inner music of Shafi’i Kadkani's poems.